2021
DOI: 10.1002/acn3.51378
|View full text |Cite
|
Sign up to set email alerts
|

No strong HLA association with MOG antibody disease in the UK population

Abstract: Improvements in assays for detecting serum antibodies against myelin oligodendrocyte glycoprotein (MOG) have led to the appreciation of MOGantibody-associated disease (MOGAD) as a novel disorder. However, much remains unknown about its etiology. We performed human leukocyte antigen (HLA) analysis in 82 MOGAD patients of European ancestry in the UK population. No HLA class II associations were observed, thus questioning the mechanism of anti-MOG antibody generation. A weak protective association of HLA-C*03:04 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 21 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…This is in line with findings that CD4+ T cells (HLA class II) dominated cell infiltrates in MOGAD patients' lesions. In a Dutch and UK study, no negative association of MOGAD to an HLA subtype could be discerned to date, whereas a Chinese study suggested an association of DQB1 * 05:02-DRB1 * 16:02 alleles to pediatric-onset MOGAD ( 210 212 ). Notably, to this date, no definite genetic association could be shown in MOGAD; specifically, no strong HLA dependence, which is in contrast to what has been suggested in MS ( 210 212 ).…”
Section: Are Mog and Mog-igg-induced Animal Models Good Models For Mo...mentioning
confidence: 94%
“…This is in line with findings that CD4+ T cells (HLA class II) dominated cell infiltrates in MOGAD patients' lesions. In a Dutch and UK study, no negative association of MOGAD to an HLA subtype could be discerned to date, whereas a Chinese study suggested an association of DQB1 * 05:02-DRB1 * 16:02 alleles to pediatric-onset MOGAD ( 210 212 ). Notably, to this date, no definite genetic association could be shown in MOGAD; specifically, no strong HLA dependence, which is in contrast to what has been suggested in MS ( 210 212 ).…”
Section: Are Mog and Mog-igg-induced Animal Models Good Models For Mo...mentioning
confidence: 94%
“…In patients with MOGAD, genetic studies showed no strong correlation between human leukocyte antigen (HLA) genotype and MOGAD development; importantly, no cause for disease pathogenesis has been found. A recent study found a protective effect of the HLA-C*03:04 allele ( 44 ), whereas a Dutch study could not find any associations ( 45 ). In addition, in a Chinese cohort, there was an association between pediatric-onset MOGAD for DQB1*05:02-DRB1*16:02, but not for adult MOGAD ( 46 ).…”
Section: T- and B-cell Mediated Pathogenesis Of Myelin Oligodendrocyt...mentioning
confidence: 83%
“…A total of 26 patients with MOGAD were selected for this study with a slight female preponderance (male-to-female ratio of 1:1.36). The UK cohort ( 15 ) also showed a slight female preponderance of 62%, with an average age of onset of 31 years (range 3–69 years). In a multi-center study ( 16 ) involving at least three US race/ethnicities (white, black, Asian and other), the proportion of women was as high as 85% (21/25).…”
Section: Discussionmentioning
confidence: 97%